Analisis Nilai-Nilai Musyawarah Pada Film Anak Indonesia “5 Elang” - Sekar Arum Pramudita; Muhamad Taufik Hidayat (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This study aimed to analyze and describe the contents of the moral values of deliberation in a movie entitled "5 Elang". The method used in this study was descriptive qualitative with a content analysis design. The data sources included scenes and dialogue among movie characters. The technique used in this study was documentation. Data were analyzed by data reduction, data presentation, and drawing conclusions. The assessment technique to check the validity of the data was the extension of observation. The results of this study indicated that "5 Elang" contains the moral values of deliberation, namely responsibility, fairness, mutual help, tolerance, togetherness, patience, honesty, mutual advice, exchange of opinions, freedom of thought, giving each other input, making decisions, and consensus. The implications of this study were: (1) teachers can provide students with an understanding of the inculcation of deliberative values through screening Indonesian children's films in the classroom; (2) parents must pay attention to the shows that children can watch to obtain good educational knowledge so that moral values can be applied, especially the value of deliberation in daily life. This study revealed the contents of deliberation values in elementary schools through Indonesian children's movies in a comprehensive way.